Can Higher Wages Protect Your Heart? Regional Evidence from Romania - Cristian Incaltarau; Adrian-Vasile Horodnic; Doru Botezat (CES Working Papers, 2015)
There is a bilateral influence between health and economic development. On the one hand, population health influences economic performance, both at micro and macro levels. On the other, being reflected in higher wellbeing, economic performance also influences health of population. Therefore, according to the materialist view, health status is dependent on the standard of living, whereas low living standards can increase the probability of morbidity and mortality by feeding poverty, poor hygiene and restricting access to health care and education, which is truly important in preventing diseases. Being generally considered to be a representative indicator for the standards of living, we have assessed the impact of wage variations on cardiovascular diseases (CVD) mortality, as CVD were proved to be more sensitive to socio-economic conditions, but also generally the main mortality cause in post-communist countries including Romania. Carrying out a panel data analysis over the 1995-2012 period on Romanian NUTSIII regions, the results showed a direct link between wage level and CVD mortality proving that the higher wages reach, the lower mortality is, thus confirming assumed materialist hypothesis.
Keywords: J31; I14; 330; wage level; cardiovascular diseases; mortality; Romania; panel data analysis